What ever happened to Germany? Is the decline of the former European key currency country caused by structural sclerosis or macroeconomic mismanagement? - Eckhard Hein; Achim Truger (Technische Universität Darmstadt, Department of Law and Economics, 2004)
This paper challenges the institutional sclerosis view of the German crisis according to which rigid labour markets and generous welfare state institutions have driven Germany into its position as "Europe's sick man". In general, the view is not convincing, because the underlying hypotheses about the effects of labour market regulation and welfare state institutions on employment and growth cannot unambiguously be derived from modern labour market theory and are at least partially at odds with accepted empirical findings. In particular, the explanation is unconvincing, because in international comparison Germany's labour market and welfare state institutions are simply not as sclerotic as often supposed. In most of the aggregate indicators for structural rigidities Germany is not worse than the average OECD or EU country. Moreover, there is a macroeconomic explanation focusing on the combined effects of restrictive and pro-cyclical monetary, fiscal and wage policies in Germany that is broadly consistent with modern macroeconomic theory and is supported by empirical data
Keywords: 330; Wirtschaftswachstum; Konjunkturpolitik; Arbeitsmarktflexibilisierung; Sozialstaat; Deutschland